PO 18120 - Eccrine poroma associated with a poroid hidradenoma in a large single lesion over the foot: case report - Ryuko Cândido Nishikawa, Danilo; Leite da Silva, Ana Caroline; Aires Duarte, Fernando; Honda Saito, Guilherme; Monteiro, Augusto César; Pires Prado, Marcelo (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Eccrine poroma (EP) and poroid hidradenoma (PH) are rare benign neoplasms derived from eccrine sweat glands of the epithelium. Both are variants of poroid neoplasms and rarely become malignant. This report describes the clinical presentation, radiographic and pathological features as well as the treatment of a rare association of EP and PH in a large single lesion over the foot. Case Report: We present a 55-year-old male patient with a large soft tissue mass over the midfoot (approximately 7 cm in length and 4 cm width). It started as a hyperchromic black spot on the skin and has slowly grown over the last eight years. One year prior, pain increased significantly. There was no history of trauma, infection or other tumor in this part of the foot. In the physical exam, the tumor had well-defined edges, fibroelastic consistency and was not adherent to the surrounding soft tissue. Preoperative planning included radiographic exams: X-ray and magnetic resonance imaging (MRI). On the MRI, the tumor showed a low signal intensity on T1-weighted images, with heterogeneous high and low signal intensities on T2-weighted images. Strong contrast enhancement was observed after intravenous gadolinium administration in the base portion. The peripheral portion showed a low signal intensity without enhancement. We decided on total resection, and the procedure was performed in January of 2017. The surgical approach was a longitudinal dorsomedial incision over the first ray starting from the ankle joint to the distal third of the first metatarsal. The entire tumor was excised with clean margins and sent for anatomopathological analysis and histopathological examination. Histopathologic examination showed that the tumor was a poroid neoplasm consisting of both dermis (poroid hidradenoma) and epidermis (eccrine poroma) components. There were no features of malignancy. After 20 months of surgery, patient remains asymptomatic with no signs of recurrence of the tumor. Conclusion: Skin tumors must be born in mind in the differential diagnosis of a chronic mass in the foot. Surgical treatment for this type of tumor is curative and prevents recurrence and malignant change.